Implementation of elementary school physical education quantity and quality law through school district audit, feedback, and coaching - Hannah R. Thompson; Kristine A. Madsen; Maya Zamek; Thomas L. McKenzie; David A. Dzewaltowski (BMC, 2023)
Abstract Background To address low state physical education (PE) quantity and quality law implementation in elementary schools, the New York City Department of Education (NYCDOE) delivered a multilevel intervention (PE Works; 2015-2019), which included a district-led audit of school PE-law implementation, feedback, and coaching with principals. Using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) implementation science framework, we assessed the primary multilevel drivers of success for this approach in increasing adherence to PE quantity and quality law. Methods We conducted in-depth, semi-structured interviews with district-level personnel (n=17), elementary school administrators (n=18), and PE teachers (n=6) in 2020-21. Results Interview results suggested several key RE-AIM drivers of successful PE law implementation. Reach: Ensure higher-need schools receive the necessary initial support to improve PE and later focus on lower-need schools. Effectiveness: Provide support tailored to school needs, not penalties, to improve PE. Adoption: Increase the priority of PE at both district and school levels (e.g., audit and feedback, themselves, appear to elevate PE's priority). Streamline data collection and feedback reports; collecting/reporting too much information is burdensome and leads to lack of focus. Involve qualified (i.e., skilled in both school administration and PE programming/pedagogy) district-level personnel to work collaboratively with schools. Implementation: Build strong, trusting district-school relationships. Maintenance: Provide ongoing district-level support to schools and involve parents to advocate for quality PE. Conclusions PE audits, feedback, and coaching (PEAFC) can guide schools in establishing long-term plans for successfully implementing PE-related law. Future research should examine the impact of PEAFC elsewhere (e.g., secondary schools, other districts).